Detection of Organochlorine Pesticides Residues in Garlic and Evaluation of Health Risks - ASLAN, Şükran; İÇLİ, Nesrin (Turk Tarim ve Doga Bilimleri Dergisi, 2022)
Persistent organic polluting pesticides that have been used extensively historically can still be detected in agricultural products and cause health risks. In this study, banned organochlorine pesticide (OCP) residue levels in 23 garlic samples produced in the fields of different villages located in the potentially polluted area in the center of Kastamonu were determined by GC/MS method combined with QuEChERS extraction and clean-up technique. In our study, at least one OCP was detected in 14 of 23 samples and 20 of the 23 OCPs we examined in our study, were detected in at least one sample. The most frequently detected OCP residue in garlic is dichloro-diphenyl-trichloroethane (DDT) and its metabolites. The residue levels of all garlic samples were below their maximum residue levels (MRL), except for sample 16. Eighteen of the OCPs we examined in our study, were determined in sample 16 and 14 of them had very high concentrations. Estimated daily intake levels (EDI) of all samples were calculated to determine whether the acceptable daily intake (ADI) levels were exceeded in order to make a risk assessment. None of the EDI values calculated from the amounts of residues in the sample 16 exceeded the ADI levels. However, it should not be forgotten that samples such as sample 16 may pose a risk of exposure for people whose actual consumption of garlic is higher than the calculated amount.
Keywords: Gıda güvenliği; GC-MS; OCP; Pestisitler; QuEChERS; Toksisite; Food safety; GC-MS; OCPs; Pesticides; QuEChERS; Toxicity; 2. Zero hunger; 13. Climate action; 3. Good health